SPATIAL AND TEMPORAL VARIATION OF INDONESIAN THROUGHFLOW IN THE MAKASSAR STRAIT - Agus S. Atmadipoera; Selfrida M. Horhoruw; Mulia Purba; Dwi Y. Nugroho (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Using outputs of INDESO model, this study investigated vertical structure, spatial and temporal variation of the Indonesian Throughflow in Makassar Strait (M-ITF). It was shown that the main axis of persistent southward jet of M-ITF formed a unique path following the western shelf slope along the strait, which was associated with a high kinetic energy (KE) region from near-surface down to the thermocline layer. Furthermore, a drastic jump of KE appeared in the narrow and deep Libani Chan-nel (near 3°S) where the strait's width shrinks significantly, thus an elevated flow velocity was needed to maintain transport volume balance. Here, maximum southward velocity at thermocline exceeded 1.2 m/s. Spatial pattern of M-ITF can be described by the first EOF mode which accounts for 79 % of the total variances. It exhibited that contours of the flow amplitudes were similar to M-ITF path, and the largest amplitude was located near the Libani Channel. Out-of-phase relationship of the flow was found between M-ITF and eddies circulation that developed in the edges of the strait. Corresponding temporal fluctuation of the first EOF mode indicated that M-ITF variabilities varied from intra-seasonal to inter-annual scales. Annual fluctuation of M-ITF was seen from EOF mode-2 (at thermocline layer) and mode-3 at lower-thermocline. Cross-spectra analysis revealed that variability of M- ITF (e.g. on annual scale) at northern entrance was highly coherent to the fluctuations of North Equatorial Current (NEC) and Mindanao Current (MC), suggesting that variability of M-ITF was remotely influenced by the Pacific low-latitude western boundary currents. Keywords: INDESO model, Indonesian Throughflow, Makassar Strait, EOF, Cross-Spectra Analysis